Effect of plant spacing on the soil properties and fertility of Pinus sylvestris var. mongolica plantations in sandy land of the agro-pastoral ecotone in northern China - Guo, Xinyu; Yang, Guang; Ma, Yunxia; Qiao, Shi; Chen, Haoyu; Liu, Feng; Ma, Shuai (Frontiers in Environmental Science, 2025)
Duolun County in Inner Mongolia, a typical agro-pastoral ecotone, serves as an important ecological barrier in northern China. To combat windblown sand and land degradation, the government has established extensive P. sylvestris var. mongolica Litv. plantations. This study investigated the effects of three afforestation modes (2 m × 6 m, 2 m × 3 m, and 1 m × 1 m), which were used as treatments, and unafforested bare sandy land as a control, on soil physicochemical properties and soil fertility. The results showed that row spacing significantly affected soil characteristics and soil fertility. With an increase in plant row spacing, the content of coarse particles decreased, while fine particle content, soil water and nutrient levels, and soil porosity increased. Additionally, the bulk density of the soil decreased, particularly in the topsoil. However, planting P. sylvestris var. mongolica in sandy land increased the soil’s electrical conductivity, which declined with wider spacing. Soil fertility of different types of plantation forests was evaluated using the soil quality index (SQI) and grey relation analysis (GRA) combined with the minimum dataset (MDS), and the results showed that: 2 m × 6 m > 2 m × 3 m > 1 m × 1 m > bare sandy land. The results of the two evaluation systems were consistent and their TDS (total dataset) and the MDS in the two evaluation systems were significantly positively correlated (SQI: P < 0.05, R2 = 0.9384). GRA: P < 0.05, R2 = 0.8929). Compared with bare sand, the soil bulk density and pH of 2 m × 6 m plantation was 13.72% and 4.02% lower; the soil water content and total porosity were 49.75% and 27.88% higher; the soil organic matter, total N, P, and K were 250.99%, 136%, 100%, and 19.53% higher; the available N, P, and K were 29.95%, 94.3%, and 12.71% higher; and the clay, silt and very fine sand contents were 242.55%, 343.1%, and 17.21% higher, respectively. These findings indicate that the development of soil characteristics and fertility accumulation are not ideal when the planting density is larger, among the above three afforestation modes, 2 m × 6 m plantation forests can better improve the soil characteristics and fertility quality of sandy soils.